2019
DOI: 10.1016/j.ejor.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

To what extent can new web-based technology improve forecasts? Assessing the economic value of information derived from Virtual Globes and its rate of diffusion in a financial market

Abstract: To what extent can new web-based technology improve forecasts? Assessing the economic value of information derived from Virtual Globes and its rate of diffusion in a financial market,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 92 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…This is confirmed by conducting a log-likelihood ratio test (LLR) to analyse whether the improvement in explanatory power observed by incorporating the Temp variable in Model II is statistically significant. In particular, we calculated LLR = 2[LL Model II − LL Model I ], where LLModel II and LLModel I are the log-likelihoods of Model II and Model I, respectively (see Green et al, 2019). We found that LLR = 5.6 (χ 1 2 [0.05] = 3.841).…”
Section: The Impact Of Temperature On the Favourite-longshot Biasmentioning
confidence: 99%
“…This is confirmed by conducting a log-likelihood ratio test (LLR) to analyse whether the improvement in explanatory power observed by incorporating the Temp variable in Model II is statistically significant. In particular, we calculated LLR = 2[LL Model II − LL Model I ], where LLModel II and LLModel I are the log-likelihoods of Model II and Model I, respectively (see Green et al, 2019). We found that LLR = 5.6 (χ 1 2 [0.05] = 3.841).…”
Section: The Impact Of Temperature On the Favourite-longshot Biasmentioning
confidence: 99%